Does Vitamin D Deficiency Increase the Risk of Autism Spectrum Disorder? Linking Evidence with Theory—A Narrative Review - Sadia Sultan; Noor Alhejin; Raed Serafi; Manar Abu Alrahi; Gehad Afifi; Layan Al-Adawi; Mohammed Serafi; Nada El Madhoun (Psychiatry International)
Introduction: Vitamin D plays a crucial role in brain health by providing antioxidant, anti-inflammatory, and neuroprotective benefits. It regulates neurotransmitters and neurotrophins that are essential for the development, maintenance, and functioning of the nervous system. Deficiency in vitamin D during pregnancy and early childhood can disrupt neurodevelopment, potentially contributing to autism spectrum disorder (ASD). The aim of this narrative review was to analyze the potential link between vitamin D deficiency and the development of ASD, as well as to explore the therapeutic benefits of vitamin D supplementation. Method: We performed a literature search across PubMed, EMBASE, Web of Science, and the Cochrane Library databases, reviewing observational studies, randomized controlled trials (RCTs), and meta-analyses for evidence of an association between vitamin D deficiency and ASD. Results: The results were mixed but promising, with most observational studies suggesting a positive link between vitamin D deficiency and ASD, though these findings were not consistently replicated in prospective studies or RCTs. In conclusion, the available data are insufficient to establish vitamin D deficiency as a definitive cause of ASD. Further RCTs, particularly during pregnancy and infancy, are needed to better understand the role of vitamin D in the etiology of ASD and its potential as a therapeutic intervention. Conclusions: The current available data are insufficient to support vitamin D deficiency as a definitive factor in the etiology of autism spectrum disorders. To translate this hypothesis into clinical practice, additional randomized controlled trials, particularly during pregnancy and early infancy, are needed.